Conception of teachers of biology, physics and chemistry about the problem-based learning (PBL) - Moreno, Mauro Antônio; Reis, Márcio José dos; Calefi, Paulo Sergio (Revista Hipótese, 2016)
Problem-Based Learning (PBL) is a methodology which seeks to address the knowledge in an inter-related and contextualized way which can be able to engage students in an active process of reflection and construction of their own knowledge. This study aimed to investigate the concepts of teachers of biology, physics and chemistry about the PBL. The research subjects were 11 teachers from public schools who attended a extension course entitled "Problem-Based Learning in classes of biology, physics and chemistry." The results showed that teachers understand the methodology, find it interesting, but, they refuse to use it because it requires a more comprehensive training.
Keywords: Problem based learning; Active methodology; Chemistry teaching